2020
DOI: 10.1038/s41467-020-19713-w
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput laboratory evolution reveals evolutionary constraints in Escherichia coli

Abstract: Understanding the constraints that shape the evolution of antibiotic resistance is critical for predicting and controlling drug resistance. Despite its importance, however, a systematic investigation of evolutionary constraints is lacking. Here, we perform a high-throughput laboratory evolution of Escherichia coli under the addition of 95 antibacterial chemicals and quantified the transcriptome, resistance, and genomic profiles for the evolved strains. Utilizing machine learning techniques, we analyze the phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 64 publications
7
62
0
Order By: Relevance
“…It is worth noting that antibiotic-induced genomic alterations including deletions, rearrangements, and amplification have been reported in many laboratory-evolved antibiotic resistant bacterial strains (Sandergren and Anderson, 2009). Several laboratory-evolved antibiotic resistant Escherichia coli strains also appeared to carry more than 20 mutations (Maeda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that antibiotic-induced genomic alterations including deletions, rearrangements, and amplification have been reported in many laboratory-evolved antibiotic resistant bacterial strains (Sandergren and Anderson, 2009). Several laboratory-evolved antibiotic resistant Escherichia coli strains also appeared to carry more than 20 mutations (Maeda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that antibiotic-induced genomic alterations including deletions, rearrangements, and amplification have been reported in many laboratory-evolved antibiotic-resistant bacterial strains ( Sandegren and Andersson, 2009 ). Several laboratory-evolved antibiotic-resistant E. coli strains also appeared to carry more than 20 mutations ( Maeda et al, 2020 ). Tetracycline-induced genome rearrangements led to the loss of 6.1 kb having seven full-length and two truncated genes in E. coli strains ( Hoeksema et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of tight matches between mutational, genetic, and macroevolutionary variances in Drosophilid wing shape (Houle et al, 2017) is exemplary of a successful phenomic project. Second, large-scale empirical studies of the genotype-phenotype map will finally become possible, because of the availability of high-throughput phenotypic data and analytical framework to deal with big data (Pitchers et al, 2019;Zheng et al, 2019;Maeda et al, 2020). Third, studies of fossil time-series will gain opportunities to document and analyze the dynamics of long-term phenotypic evolution with unprecedented temporal resolution (Brombacher et al, 2017;Liow et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained using Grad-CAM suggested that the morphological features of the ENX-resistant strains could be found mainly at the envelope, and this led us to consider which genes might be associated with the morphological characteristics of these strains. (3) in Methods]. We retained pairs of genes and image features meeting the condition that the absolute correlation coefficient between them was equal to or greater than 0.999.…”
Section: Correlation Of Image Features With Gene Expressionmentioning
confidence: 99%
“…Laboratory-based bacterial evolution is a powerful tool for investigating the dynamics of acquired drug resistance. 1,2,3 In these experiments, bacterial cells are exposed to fixed concentrations of drugs, around which cell growth is partially or completely inhibited such that a selective advantage for resistant strains is maintained. Recently, Suzuki et al performed laboratory evolution of Escherichia coli under various drug treatment conditions to obtain resistant strains, including those resistant to quinolones such as enoxacin (ENX).…”
Section: Introductionmentioning
confidence: 99%